Hippocampal spindles and barques are normal intracranial electroencephalographic entities. Issue 12 (December 2021) - Kokkinos, Vasileios; Hussein, Helweh; Frauscher, Birgit; Simon, Mirela; Urban, Alexandra; Bush, Alan; Bagić, Anto I.; Richardson, R. Mark
Highlights: Hippocampal spindles and barques occur equally often in temporal lobe epilepsy (TLE) and non-TLE by both noninvasive and intracranial EEG criteria. In patients with seizure-free surgical outcome, barques were more prominent in extra-temporal TLE. The presence of barques may signify lack of epileptogenic properties in the underlying hippocampus. Abstract: Objective: To assess whether hippocampal spindles and barques are markers of epileptogenicity. Methods: Focal epilepsy patients that underwent stereo-electroencephalography implantation with at least one electrode in their hippocampus were selected (n = 75). The occurrence of spindles and barques in the hippocampus was evaluated in each patient. We created pairs of pathologic and pathology-free groups according to two sets of criteria: 1. Non-invasive diagnostic criteria (patients grouped according to focal epilepsy classification). 2. Intracranial neurophysiological criteria (patient's hippocampi grouped according to their seizure onset involvement). Results: Hippocampal spindles and barques appear equally often in both pathologic and pathology-free groups, both for non-invasive (Pspindles = 0.73; Pbarques = 0.46) and intracranial criteria (Pspindles = 0.08; Pbarques = 0.26). In Engel Class I patients, spindles occurred with similar incidence both within the non-invasive (P = 0.67) and the intracranial criteria group (P = 0.20). Barques were significantly more frequent in extra-temporal lobe epilepsy defined by either non-invasive (P = 0.01) or intracranial (P = 0.01) criteria. Conclusions: Both spindles and barques are normal entities of the hippocampal intracranial electroencephalogram. The presence of barques may also signify lack of epileptogenic properties in the hippocampus. Significance: Understanding that hippocampal spindles and barques do not reflect epileptogenicity is critical for correct interpretation of epilepsy surgery evaluations and appropriate surgical treatment selection.